Crescimento de leguminosas arbóreas e rendimento de milho em sistemas silviagrícolas - Oliveira, Vianney Reinaldo de (2012)
One way to reduce costs in the establishment of forest plantations is to plant annual crops intercropped with the tree species. Two experiments were conducted in the same area in consecutive years. The objectives were to evaluate the agronomic and economic viability of intercropping of sabiá (Mimosa caesalpiniifolia) and gliricídia (Gliricidia sepium) with corn (Zea mays), and the influence of the proximity of these plants legume species on green corn-cob profit and maize kernels. In the experiment-l, the legumes were cultivated in monoculture and intercropped with maize cultivar AG 1051, in randomized blocks with five replications. Three rows of corn were planted between two rows of each legume. In experiment-2, the legumes were cut to 0.5 m from ground level at the time of sowing corn, and the young branches and leaves were incorporated into the cultivated areas in the consortium. Tree species showed linear increase in plant height and diameter of the crown and neck, in monoculture and in consortia. Intercropping increased the plant height in the sabiá, but did not affect this feature in gliricídia. Gliricídia had lower plant height than the sabiá. There were no differences between tillage systems or between species in the canopy diameter. Intercropping reduced the stem diameter of gliricídia, but did not alter this characteristic in sabiá, which had lower stem diameter that gliricídia. Intercropping reduced the yield of green corn-cobs, but it did not influence the grain yield. The row on the left produced more mass marketable husked green corn-cobs than the central and right rows, but the mass of grain growth was higher in the central row. Despite this reduction, in some cases, with respect to the growth of legumes, maize rotation is advantageous in the reduction of these species implementation costs, especially when maize is marketed in the form of green corn-cob. In experiment-2, intercropping reduced only the total number and weight of green corn-cobs and grain profit and number of mature ears, but it did not influence the number and mass of marketable green corn-cobs with husk and without husk. The row on the left produced a greater profit of green corn-cobs than the central and right rows, but the profit was not influenced by the position of the row. There were no differences among tree species with respect to their effects on green corn-cobs profit and grain yield in the corn rows